Стратегическая Основа Исламского Популизма: Сравнительная Оценка Его Роли В Президентских Выборах В Индонезии В 2019 И 2024 Годах (THE STRATEGIC FABRIC OF ISLAMIC POPULISM: A COMPARATIVE ASSESSMENT OF ITS ROLE IN INDONESIA'S 2019 AND 2024 PRESIDENTIAL ELECTIONS) - Rahmat Syahid Suraya; Dmitry Ivanovich Pobedash (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
This study examines the evolving role of Islamic populism in Indonesia’s 2019 and 2024 presidential elections, focusing on its strategic deployment and sociocultural implications. In the 2019 election, Islamic populism was characterized by confrontational narratives, portraying the Muslim community as the moral majority opposed to a corrupt elite. In contrast, the 2024 election saw a strategic moderation of Islamic populism, blending religious appeals with messages of national unity and pluralism. This paper argues that Islamic populism in Indonesia is not a rigid ideological movement but a flexible, strategic tool that adapts to changing political and societal dynamics. The study leverages a wide range of sources, including academic literature and data level Islamic Populism in Indonesia, to dissect their implications for Indonesia's political landscape. Through a qualitative comparative analysis, the study highlights the continuity and change in the deployment of Islamic populism and discusses its implications for Indonesia’s democratic resilience and Islamic social culture. The study concludes a discernible trend: successful candidates are those who skillfully merge Islamic values with a broader, pluralistic appeal and strategically align themselves with the incumbent president's supportive network. Keywords: Populism, Islam, Indonesia, Religious Identity, Presidential elections.